2020
DOI: 10.1002/jbt.22494
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐23b functions as an oncogenic miRNA by downregulating Mcl‐1S in lung cancer cell line A549

Abstract: It has been reported that microRNA‐23b (miR‐23b) plays a role in multiple cancers, while its impact on lung cancer has not been comprehensively known. Our study explored the probable impacts of miR‐23b on lung cancer cells. Expression of miR‐23b was assessed by reverse transcription quantitative polymerase chain reaction. After miR‐23b mimic, inhibitor, and their own control were transfected into A549 cells, cell viability, migration, invasion, apoptosis, and epithelial‐mesenchymal transition (EMT) were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, miR-23b was identified to act both as an oncogene and as a tumor suppressor. Increased expression of miR-23b promoted lung cancer cells viability, migration, invasion, and EMT [ 56 ]. miR-23b inhibits cell migration and invasion through targeting phosphodiesterase 7A (PDE7A) in colon cancer cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-23b was identified to act both as an oncogene and as a tumor suppressor. Increased expression of miR-23b promoted lung cancer cells viability, migration, invasion, and EMT [ 56 ]. miR-23b inhibits cell migration and invasion through targeting phosphodiesterase 7A (PDE7A) in colon cancer cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we identified some possible binding microRNAs of Lnc-PLA2G4A-4 by bioinformatic prediction, which were reported to regulate tumor progression, such as miR-23b, miR-567 and miR-888. Among them, miR-23b-3p attracted our attention, because it acts as both a tumor suppressor [ [35] , [36] , [37] ] and an oncogenic miRNA [ [38] , [39] , [40] ] in various types of carcinogenesis. There is accumulating evidence that miR-23b performed a variety of functions in various tumor progressions, which is involved in proliferation [ 41 ], apoptosis [ 42 ], metastasis [ 43 ], angiogenesis [ 44 ], chemoresistance [ 45 ] and glycolysis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-425 has been demonstrated to promote cell proliferation, migration, invasion and EMT by activating the β-catenin pathway (29). miR-23b is involved in tumor-promoting effects, which are associated with the activation of the JAK/STAT and Wnt/β-catenin pathways in A549 cells (30). In addition, the key EMT factor, ZEB1, is transcriptionally regulated by the β-catenin/TCF4 complex (11).…”
Section: Discussionmentioning
confidence: 99%